Pengaruh Pelanggaran Lalu Lintas Terhadap Potensi Kecelakaan Pada Pengendara Sepeda Motor di Kota Kupang (Studi Kasus Mahasiswa Universitas Nusa Cendana) - Betan, Yosefina Kemohun Kewa; Frans, John Hendrik; Bunganaen, Wilhelmus (Universitas Nusa Cendana, 2024)
Traffic violations that are mostly caused by motorcyclists can cause accidents. The purpose of this study is to determine the characteristics of students of Nusa Cendana University Kupang who ride motorcycles and determine the effect of traffic violations in students of Nusa Cendana University Kupang. The research method used binary logistic regression with IBM SPSS 25. The result showed that students of Nusa Cendana University who had a driver’s license were 77% and those who did not have a driver’s license were 23%. For traffic violations that affect the potential for accidents, namely against the current (0.049), not using a helmet (0.042), operating a cellphone while driving (0.033), not installing mirrors (0.029), changing movements suddenly without a sign light (0.028), reckless driving (0.024), overtaking from the wrong side (0.021), carrying more than one passenger (0.016), parking out of place (0.004), violating red lights (0.003), not paying attention to signs (0.002), talking to other drivers (0.001), not using motorcycle equipment (0.001), under the influence of alcohol (0.0001).